Ideology, Humanity, and Freedom in Ha Jin’s Waiting - Hasnul Insani Djohar (Insaniyat : Journal of Islam and Humanities, 2020)
This paper examines how Ha Jin’s Waiting challenges the Maoist communist regime by depicting the protagonist, Lin, as struggling to fight for his rights to live freely. The Maoist regime successfully establishes “normalizing power” in a society to lead the protagonist to believe that the goal of his life is mainly for working hard for the military institution and the regime, instead of establishing his freedom. As a result, Lin loses his senses of humans, such as love and empathy, and lives with selfishness and ignorance as to the way the Maoist discourse teaches him through Mao’s red book. By engaging with cultural studies, this paper investigates how Jin’s Waiting challenges Maoist ideology by both celebrating and critiquing the idea of capitalism, which likely perpetuates communism. Thus, this paper discovers how Ha Jin’s novel challenges communist ideologies and totalitarian rules by illuminating social disorder and loses of sense of humanity. Indeed, individuals live under oppression and they are like a prisoner who is suffering from being judged and punished by totalitarian regimes and dominant society. Hence, the significance of this research is to help to reduce any forms of oppression experienced by many ethnic-Americans who have suffered from the totalitarian rulers that have ruled society, especially in the era of communism, colonialism, and global capital transnationalism.